2013
DOI: 10.1002/cncy.21371
|View full text |Cite
|
Sign up to set email alerts
|

Utility of fine‐needle aspiration and core biopsy with touch preparation in the diagnosis of renal lesions

Abstract: BACKGROUND: Cytologic evaluation by fine-needle aspiration (FNA) and core biopsy (CB) with touch preparation (TP) is used in the diagnosis of renal lesions. METHODS: Consecutive image-guided FNA and CB, with or without TP, of renal lesions were reviewed. The cytology diagnoses were correlated with the radiology, surgical specimens, and clinical course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…Scanga and Maygarden, in a more recent study of 154 renal mass biopsy procedures, found slightly better results, with satisfactory specimen adequacy in 86 % of FNAs; core biopsies yielded satisfactory specimens in 94 % of cases [36]. Their results corroborate those of a previous study in which a higher rate of inadequate sampling was found in FNAs (11 %) versus core biopsy (3 %) [37].…”
Section: Fine-needle Aspirations (Fnas) Versus Core Biopsysupporting
confidence: 82%
See 1 more Smart Citation
“…Scanga and Maygarden, in a more recent study of 154 renal mass biopsy procedures, found slightly better results, with satisfactory specimen adequacy in 86 % of FNAs; core biopsies yielded satisfactory specimens in 94 % of cases [36]. Their results corroborate those of a previous study in which a higher rate of inadequate sampling was found in FNAs (11 %) versus core biopsy (3 %) [37].…”
Section: Fine-needle Aspirations (Fnas) Versus Core Biopsysupporting
confidence: 82%
“…Core biopsy gives more specific information than FNA for histologic tumor classification and grading [36]. In a study of 351 renal masses where both FNA and core biopsy samples were obtained, 21.6 % of the FNAs were diagnostic when the core biopsy was non-diagnostic [39].…”
Section: Fine-needle Aspirations (Fnas) Versus Core Biopsymentioning
confidence: 99%
“…Several studies have been performed by means of fluorescence in situ hybridization, and one field of research is aimed at defining which set of alterations can be held as "typical" of specific tumor subtypes. Anyway, this procedure is still investigational [16,[18][19][20][21].…”
Section: Srms: the Role Of Biopsiesmentioning
confidence: 98%
“…Although FNA is both accurate and sufficient for diagnosing most common RCCs, most of the unusual RCCs require additional tissue for testing, meaning that the use of cell blocks and core needle biopsies are likely to become more critical, primarily to ensure adequate tissue for testing …”
Section: Introductionmentioning
confidence: 99%